(untitled) (Mokslo taikomieji tyrimai / Applied Research, 2023)
With the rise of modern technologies and the implementation of new businesses and brands, the urge for publicity has generated a demand for advertisements. As the key factor for spreading awareness and attracting new consumers, advertising has gained power by employing the written word as the best means of communication. Social media platforms (Facebook, Instagram, Twitter, Pinterest and many others) are chosen more and more often as they are used by a profuse number of potential customers. A lot of companies have acknowledged that thoughtfully chosen linguistic tools might enhance the popularity of the promoted product or service. Thus, the article aims to unveil the effectiveness of phonetic and semantic devices in advertisement slogans, analyse linguistic peculiarities that boost public interest and curiosity, specify which linguistic techniques evoke most of the emotions and make the advertisement both gripping and memorable. The research was based on the application of theoretical and descriptive comparative linguistic analysis methods. Having analysed a great many advertisement slogans, the number of samples carefully elucidated and presented in this article was 13, as they contained the required linguistic segments set in the objectives of this research, i.e., onomatopoeia, alliteration, rhyme, and rhythm, as well as denotative and connotative elements of the lexical meaning. The article reveals that the proper use of linguistic devices benefits to attract and manipulate the target audience; phonetic devices enable to reach the effect of memorability, whereas semantic devices play a crucial role in the domain of emotions.